Health status of children and young persons with congenital adrenal hyperplasia in the UK (CAH-UK): a cross-sectional multi-centre study. Issue 4 (16th September 2022) - Bacila, Irina; Lawrence, Neil Richard; Mahdi, Sundus; Alvi, Sabah; Cheetham, Timothy D; Crowne, Elizabeth; Das, Urmi; Dattani, Mehul Tulsidas; Davies, Justin H; Gevers, Evelien; Krone, Ruth E; Kyriakou, Andreas; et al.
Abstract: Objective: There is limited knowledge on the onset of comorbidities in congenital adrenal hyperplasia (CAH) during childhood. We aimed to establish the health status of children with CAH in the UK. Design and methods: This cross-sectional multicentre study involved 14 tertiary endocrine UK units, recruiting 101 patients aged 8–18 years with classic 21-hydroxylase deficiency and 83 controls. We analysed demographic, clinical and metabolic data, as well as psychological questionnaires (Strengths and Difficulties (SDQ), Paediatric Quality of Life (PedsQL)). Results: Patient height SDS in relation to mid-parental height decreased with age, indicating the discrepancy between height achieved and genetic potential height. Bone age was advanced in 40.5% patients, with a mean difference from the chronological age of 1.8 (±2.3) years. Patients were more frequently overweight (27%) or obese (22%) compared to controls (10.8% and 10.8%, respectively, P < 0.001). No consistent relationship between glucocorticoid dose and anthropometric measurements or hormonal biomarkers was detected. A small number of patients had raised total cholesterol (3.0%), low HDL (3.0%), raised LDL (7.0%) and triglycerides (5.0%). SDQ scores were within the 'high' and 'very high' categories of concern for 16.3% of patients. 'School functioning' was the lowest PedsQL scoring dimension with a median (interquartile range) of 70 (55–80), followed by 'emotional functioning' with a median of 75 (65–85). Conclusions: Our results show an increased prevalence of problems with growth and weight gain in CAH children and suggest reduced quality of life. This highlights the urgent need to optimise management and monitoring strategies to improve long-term health outcomes.